Superadditivity of functionals related to Gauss' type inequalites - Varošanec, Sanja (Sarajevo Journal of Mathematics, 2024)
In this paper we prove superadditivity of some functionals associated with the Gauss-Winckler and the Gauss-Pólya inequalities.